Pediatric Mitochondrial Disease: Experience from A Tertiary Care Hospital in Bangladesh - Fatema, Kanij; Dola, Farah Naz (Bangladesh Journal of Child Health, 2024)
Background: Mitochondrial diseases are rare group of heterogeneous, genetically determined disorders that affect multiple organs with variable severity due to the dysfunction of mitochondria. They usually present with acute or chronic features with intermittent decompensation. The common features are neuro-regression, hypotonia, failure to thrive, stroke, seizures, myopathy, cardiomyopathy, deafness, blindness, movement disorder, lactic acidosis etc. The aim of this study was to describe the clinical, neuroimaging and genetic analysis of mitochondrial diseases. Methodology: This retrospective study was done among sixteen admitted patients in the Department of Pediatric Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2016 to December 2023. Results: Total sixteen patients were included in the study. The age of the patients ranged from 3 months-8 years; 11 patients were male. Developmental delay and regression, seizure, hypotonia, dystonia, ataxia were the key clinical manifestations. About 12.5% had persistent hypoglycemia. 6.13% presented with periodic paroxysms of dyskinesia and weakness. In MRI of brain, predominant feature was bilateral basal ganglia involvement. Genetic analysis showed variable presentation. Here, 12.5% was diagnosed with Leigh syndrome, 12.5% had primary carnitine deficiency, 12.5% had SURF-1 mutation causing mitochondrial complex IV deficiency, 6.13% had mitochondrial short chain enoyl co-A hydratase deficiency,12.5% had mitochondrial DNA depletion syndrome and 6.13% had progressive external ophthalmoplegia with mitochondrial DNA deletions. Conclusion: Multisystem heterogenous involvement gives a clue to the suspicion of mitochondrial disease in pediatric population. Bangladesh J Child Health 2023; Vol 47 (2) : 65-71